2005
DOI: 10.1385/bter:103:2:147
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hypoxia on Contents of Essential Elements in Pika and Rat Heart

Abstract: The effects of hypoxia on the levels of essential macroelements and trace elements (K, Na, Ca, Mg, Cu, Zn, Fe, and Mn) in the heart muscles of Wistar rats and plateau pikas (Ochotona curzoniae) were studied by atomic absorption spectrometry. Unlike the rat, the plateau pika is tolerant to hypoxia. The levels of K, Na, and the trace element Mn were not significantly changed in rat or pika hearts after exposure to hypoxia for 1, 10, or 25 d at simulated altitudes of 5000 and 7000 m. Other minerals (Ca, Mg, Cu, Z… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“… 10 Many trace elements play important roles in the activation or inhibition of enzymatic reactions or the oxidant/antioxidant balance. 3 Hence, trace elements may be involved either directly or indirectly in the pathogenesis of several diseases, including COPD. 11 It has been shown that trace mineral supplementation may aid in the reduction of the period spent on mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 Many trace elements play important roles in the activation or inhibition of enzymatic reactions or the oxidant/antioxidant balance. 3 Hence, trace elements may be involved either directly or indirectly in the pathogenesis of several diseases, including COPD. 11 It has been shown that trace mineral supplementation may aid in the reduction of the period spent on mechanical ventilation.…”
Section: Discussionmentioning
confidence: 99%
“…Trace minerals play an important role in the metabolism, starting from the lowest level of intracellular life extending to the functional activity of the largest organs. 2 , 3 Pulmonary hypertension (PH) is characterized by the intimal and medial proliferation of the small pulmonary arteries, which in turn leads to the development of secondary fibrotic and plexiform vascular lesions. Increased pulmonary vascular resistance and pulmonary arterial pressures in PH constitute a life-threatening situation owing to the increase in afterload leading to right ventricular failure.…”
Section: Introductionmentioning
confidence: 99%
“…The levels of essential elements in the tissues of animals (including crustaceans) can be regulated according to the physiological condition of the specimens, while dead animals cannot perform such regulation. 31,32 In this way, dead animals release or take up elements according to their availability in seawater. This fact likely explains the differences found in elemental composition between dead and live crabs.…”
Section: Results and Discussion Element Composition According To Specmentioning
confidence: 99%
“…Several elements (Se, Cr, Cu, Mg, Zn, Li and V) are suspected of being involved in the genesis of arteriosclerotic heart disease [ 11 ]. Cu and Fe are involved in many aspects of energy metabolism and are important in the synthesis of hemoglobin, myoglobin and cytochromes [ 12 ]. Se deficiency disturbs the optimal functioning of several cellular mechanisms and may promote the development of atherosclerosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Low Se concentration is also a risk factor for arterial hypertension and myocardial infarction, and a factor aggravating symptoms of myocardial ischemia [ 10 ]. Some trace elements modulate functions of cellular pro- and antioxidant systems [ 10 ], e.g., Cu, Zn and Mn protect against the effects of increased free reactive oxygen species via Cu-Zn superoxide dismutase and Mn superoxide dismutase [ 12 ]. This is of great importance, as the heart is prone to oxidative damage as it has lower activity of antioxidant enzymes (e.g., superoxide dismutase) than other tissues (e.g., liver) [ 14 ].…”
Section: Introductionmentioning
confidence: 99%